KEMATIAN TANAMAN GAHARU AKIBAT SERANGAN Heortia vitessoides Moore DI MUARA KEMBANG, KUTAI KERTANEGARA - Ngatiman Ngatiman; Erwin Erwin (Fakultas Kehutanan Universitas Mulawarman, 2020)
Gaharu (Aquilara microcarpa Baill) planted in monoculture in 2008 at Muara Kembang, Kutai Kartanegara was attacked by Heortia vitessoides Moore which resulted in the death of the plant. To explain the phenomenon of plant death, this research was conducted by observing the frequency and intensity of attacks, the effect of spacing, and pattern of pests as well. Observations were made on a 100 x 50 m striped plot with two spacing arrangements of 3 x 2 m and 2 x 2.5 m. The difference in attack frequency of H. vitessoides between the two spacing was analyzed statistically using t-test. Plant mortality with a high frequency and intensity of pest attack occurred in the 3 x 2 m spacing of the area with a monoculture planting system. Monoculture planting systems triggered patterns of attack and behavior of pests attacking throughout the year with a large number of larvae so they can eat all plant leaves. It is recommended that a mixed planting system be applied to gaharu with other useful plant species as well as to prevent and control it early if H. vitessoides pests are found before it spreads that cause plant death.